THE PROFESSIONAL PROFILE OF THE FACULTY OF EDUCATION, AT THE UNIVERSIDAD NACIONAL MAYOR DE SAN MARCOS (UNMSM) - Núñez Flores, María Isabel (2014)
The project titled: The Professional Profile of Education UNMSM, propose a study of the professional academic profile in the specialities: Mathematics and Physics, Language and Literature; History and Geography, Biology and Chemistry; English; Philosophy; Social sciences, in secondary education. The study of curriculum and its effects in the professional profile, imply to establish a relation with the scientific and philosophical conception of education, towards the professional profile. From this theoretical foundation and curricular doctrine, it is inferred the curriculum coher the student, take form in the graduate student as a product of proffessional quality and efficiency. In such way we formulat the following problem: What effects are produced by the Education curriculum in the professional academic profile of students of the Faculty of Education of the UNMSM?